Transformasi Birokrasi Melalui E-Government - Umi Arifah (LPPM IAINU Kebumen, 2020)
This study presents the implementation of bureaucratic transformation through e-government and the factors that influence the process of bureaucratic transformation. The methodology used in this study uses a library research approach, and data collection is carried out by examining and exploring journals, books and other supporting documents that are relevant to the study being conducted. The findings from this study are that e-government must be implemented seriously and consistently will greatly support the transparency of public services. Bureaucratic transformation through e-government must be carried out with the support of several factors, namely a) regulatory support, b) organizational structure, c) organizational culture, d) system renewal. In addition, if e-government is implemented seriously and consistently, it will greatly support the transparency of public services. What bureaucrats must also understand is that the use of e-government still requires a consistent monitoring system. In addition to extensive knowledge of information technology, e-government must also be supported by good integrity among policy makers and implementers. Because information technology makes things easier and more efficient.